2002
DOI: 10.1110/ps.0211102
|View full text |Cite
|
Sign up to set email alerts
|

The role of helix stabilizing residues in GCN4 basic region folding and DNA binding

Abstract: Basic region leucine zipper (bZip) proteins contain a bipartite DNA-binding motif consisting of a coiled-coil leucine zipper dimerization domain and a highly charged basic region that directly contacts DNA. The basic region is largely unfolded in the absence of DNA, but adopts a helical conformation upon DNA binding. Although a coil → helix transition is entropically unfavorable, this conformational change positions the DNA-binding residues appropriately for sequence-specific interactions with DNA. The N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 68 publications
(109 reference statements)
1
37
0
Order By: Relevance
“…The basic regions can be completely structured (e.g., ATF4; Podust et al, 2001), contain a certain amount of helical secondary structure (e.g., HY5; Yoon et al, 2006), or be completely disordered (e.g., Opaque-2; Moreau et al, 2004). Experimental evidence has suggested that, in complex with DNA, the basic regions uniformly form a-helical conformations (Hollenbeck et al, 2002). A study of conformational ensembles for 15 different bZIPs proposed that the basic regions of the bZIPs have quantifiable preferences for a-helical conformations in their unbound monomeric forms and this helicity varies from one basic region to another despite significant sequence similarity of the bZIP domains.…”
Section: Bzip Familymentioning
confidence: 99%
“…The basic regions can be completely structured (e.g., ATF4; Podust et al, 2001), contain a certain amount of helical secondary structure (e.g., HY5; Yoon et al, 2006), or be completely disordered (e.g., Opaque-2; Moreau et al, 2004). Experimental evidence has suggested that, in complex with DNA, the basic regions uniformly form a-helical conformations (Hollenbeck et al, 2002). A study of conformational ensembles for 15 different bZIPs proposed that the basic regions of the bZIPs have quantifiable preferences for a-helical conformations in their unbound monomeric forms and this helicity varies from one basic region to another despite significant sequence similarity of the bZIP domains.…”
Section: Bzip Familymentioning
confidence: 99%
“…Conservation Consensus 10 20 The first column provides the name for each bZIP-bR, 10,18,22 and the numbers in parentheses represent the net charge per residue 23 calculated based on the expected protonation states of free amino acids at neutral pH. Residues 9-18 make up the DBM.…”
Section: Bzip-brs Have Quantifiable α-Helicities That Vary With Sequencementioning
confidence: 99%
“…Furthermore, stopped-flow fluorescence experiments show that bZIP-bRs bind their cognate half-sites independently as monomers, 11,16,17 and available spectroscopic evidence suggests that, in complex with DNA, basic regions form α-helical conformations irrespective of the presence or the absence of the leucine zipper region. 18 It has been proposed that the high fraction of basic residues within basic regions destabilizes α-helical conformations in their unbound monomeric forms, thus biasing them towards heterogeneous randomcoil-like ensembles. 6,7,16,19 As a result, α-helicity within basic regions is believed to emerge as a consequence of DNA binding through an inducedfit mechanism 7,19,20 whereby disordered basic regions make sequence-specific contacts with cognate half-sites on the DNA and zipper up to form α-helices.…”
Section: Introductionmentioning
confidence: 99%
“…The peptide alone (peptide 1), the peptide conjugated at both N-and C-termini to the yeast GCN4 coil promoting sequence 30 (peptide 2), and each of these two peptides linked to a lipid core to generate LCP-1 and LCP-2 respectively. CD analysis confirmed the helical nature of the two LCPs but not the corresponding unadjuvanted peptides, irrespective of the presence of GCN4 in LCP-2.…”
Section: Discussionmentioning
confidence: 99%